ANALISIS DAMPAK TARIF IMPOR TERHADAP PERKEMBANGAN NERACA PERDAGANGAN INDONESIA (Periode 1995.1 – 2005.4) - Malik, Nazaruddin; Wulandari, Kusuma (Faculty of Economics and Business, University of Muhammadiyah Malang, 2006)
One of the used policy form government to push exporting to be natural balance of trade surplus (X>M) is with imposition of import tariff. This research aim to know tariff impact import to growth of balance of trade in Indonesia [at] period 1995.1-2005.4. By using Linier Model analysis method Dinamik (MLD) through approach of Error Correction Model (ECM), known that import tariff have an effect on positive to growth of balance of trade. Its meaning, if natural tariff of increase hence will give impact go up him growth of balance of trade (surplus) which significant.